Features of English business documentation. (Eurasian Journal of Philology Science and Education, 2015)
In this article we analyze grammatical, stylistic and lexical features of English business documentation in order to find out their influence on the translation process, also comparison of features of business style of English and Russian languages is carried out. The urgency of the research is determined by the importance of this direction oftranslation activity for economic and social development of our state and its integration into the world political, economic and social space. The special attention is paid to the problems of translation of special lexicon as its translation causes the greatest difficulties, in particular we study: problems of translation of terminology, structure of terminological units of English language, various kinds of abbreviations and their structure. On the basis of the research following conclusions have been drawn: many characteristics of business style of Russian language arepresented in English business documents nevertheless business style of English language has a lot of features that make the work of the translator much harder basically it refers to terminology and specific lexicon. Syntactic structure of English business texts is very complex; also they are full of different kinds of abbreviations and acronyms.
Keywords: business style – terms – features